2019
DOI: 10.21272/mmi.2019.4-23
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Methodology of Assessing the Potential of Countries to Attract Foreign Direct Investment

Abstract: To accelerate the transformation process in all spheres of economic and social life the relevance of the adequate assessment of the countries’ investment potential was determined in this article. The innovation process has a high impact on the investment potential of the countries through every sector of the economy. As a result, the countries competitiveness depends on the level of technological innovation. The scientific methodological approach to the estimation of countries' investment potential by the adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to the results of empirical research [47][48][49], concluded that higher innovation activity is typical of countries with higher levels of economic development.…”
Section: Financial Innovativeness and Economic Developmentmentioning
confidence: 99%
“…According to the results of empirical research [47][48][49], concluded that higher innovation activity is typical of countries with higher levels of economic development.…”
Section: Financial Innovativeness and Economic Developmentmentioning
confidence: 99%
“…Thus, it was revealed that for the insurance company, the main pluses in the running of virtual business could be: lower costs concerning the organization of the company's website; fewer costs concerning the transactions for customer service operations; «expansion of geographical diversification of company insurance products; an opportunity to increase the sale of insurance products at the expense of open access to customers from around the world; customer service on a qualitatively new level -seven days a week, 365 days a year» (Yanyshyn et al, 2019). There was also paid great attention for the research that showed the presence of healthcare in special households' groups, the way of accelerating the transformation of the management process with human resources, as well as the adequate assessment of the countries' investment potential in the content of health insurance was also deeply investigated (Antosova et al, 2019;Kasaeva, 2019). Zhang (2011) underlines that the favorable factors for the development of old-age care insurance include the aging population trend, the rising nursing costs, the high burden of the elderly, the high medical costs, and the lack of medical securityю Moreover, He and Li (2014) assessed the payment capacity of farmers; Sheng et al (2020) studied the pilot system and current situation of long-term care insurance and put forward corresponding suggestions in Suzhou.…”
mentioning
confidence: 99%